Analisa Efektifitas Perbaikan Perangkat BTS Telkomsel Karawang dengan iManager u2000 software - Felyta Emasriani; Reni Rahmadewi (STEKOM PRESS, 2021)
Recently, the need for cellular telecommunication services in Indonesia refers to a very large number. This customer growth rate must be balanced with infrastructure development. PT. Telkomsel carries out scheduled maintenance or maintenance activities on BTS devices. Based on these problems, the research carried out by the author aims to find out and understand the repair or repair procedures on computerized BTS devices at PT. Telkomsel, Karawang. The result of the research is that it is known that the application of a computerized system at PT. Telekomunikasi Selular GraPaRi Karawang helps the process of repairing BTS devices in meeting information needs. To monitor damage to BTS equipment, it is done by means of an alarm monitoring system using the iManager u2000 software.